A comparison of the effect of nanotube chirality and electronic properties on the π–π interaction of single‐wall carbon nanotubes with pyrazinamide antitubercular drug. Issue 9 (16th July 2012) - Saikia, Nabanita; Deka, Ramesh C.
Abstract Theoretical investigation on local electronic structure and stability of the π–π stacking interaction of pyrazinamide (PZA) with armchair (5, 5) and zigzag (9, 0) single‐walled carbon nanotubes (SWCNTs) is performed using density functional theory (DFT). PZA is physisorbed onto nanotube sidewall through interaction of π orbitals of PZA and SWCNT and the enhanced structural stability of PZA/SWCNT systems is due to weak side‐on rather than the head‐on π‐interactions. The physisorption of PZA onto SWCNT sidewall is thermodynamically favored; as a consequence, it modulates the electronic properties of pristine nanotube in the vicinity of Fermi region and π–π stacked interactions is stronger in (9, 0) SWCNT compared to (5, 5) SWCNT. The density of states (DOS) analysis show that PZA contributes toward the enhancement of electronic states. Projected DOS and frontier orbital analysis in the vicinity of Fermi level region suggest the electronic states to be contributed from SWCNT rather than PZA. In addition, hybrid DFT calculation which includes the dispersion correction is employed to explain the non‐covalent π–π stacking interaction between PZA and SWCNT. The local density approximation and GGA results are compared with DFT‐D to explain near about accurately the weak nonbonded van der Waals interactions between PZA and SWCNTs. © 2012 Wiley Periodicals, Inc.